HUBUNGAN PENGETAHUAN HYGIENE SANITASI DENGAN SIKAP SISWA PADA PRAKTEK MENGOLAH KUE INDONESIA DI WORKSHOP SMK N 3 MUARA BUNGO - Aprilyani Mangunsong, Siska Widya; Yusuf, Liswarti; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study was motivated by problem about the student’s attitudes has not noticed to aspects of sanitation hygiene during pratice in the workshop. The purpose of this study was to describe about student’s knowledge of sanitation hygiene and to analyze about correlation between student knowledge and attitude in the workshop.This study is a correlational study with Ex Post Facto design. Sample in this study are student of SMK N 3 Muara Bungo as many as 50 people. The instrument used are multiple choice and questionnaire likert scale. Data analyze technique used is determine the level of attainment percentage of respondent and correlation technique to know about correlation level between two variabel studied.Based on the result founded : (1) student’s knowledge is in category less well with the percentage achieved by 55,7 % (2) student’s attitude is in category well with the percentage achieved by 70 % . (3) T count in this study was 10.643. if T count greater than T table ( 10.643 > 2.000 ) indicates student’s knowledge and student’s attitude have a positive and significant correlation.Keyword : hygiene, sanitary, SMKN 3 Muara Bungo